The Staphylococcus aureus KdpDE Two-Component System Couples Extracellular K(+) Sensing and Agr Signaling to Infection Programming - Xue, Ting (American Society for Microbiology, 2011)

(untitled)
The Kdp system is widely distributed among bacteria. In Escherichia coli, the Kdp-ATPase is a high-affinity K(+) uptake system and its expression is activated by the KdpDE two-component system in response to K(+) limitation or salt stress. However, information about the role of this system in many bacteria still remains obscure. Here we demonstrate that KdpFABC in Staphylococcus aureus is not a major K(+) transporter and that the main function of KdpDE is not associated with K(+) transport but that instead it regulates transcription for a series of virulence factors through sensing external K(+) concentrations, indicating that this bacterium might modulate its infectious status through sensing specific external K(+) stimuli in different environments. Our results further reveal that S. aureus KdpDE is upregulated by the Agr/RNAIII system, which suggests that KdpDE may be an important virulence regulator coordinating the external K(+) sensing and Agr signaling during pathogenesis in this bacterium.